2016
DOI: 10.1177/0093854816637889
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors for Inpatient Aggression

Abstract: Dynamic risk and protective factors serve to assess the violence risk level of (forensic) psychiatric patients and offer guidance to clinical interventions. Risk assessment scores on Historical Clinical Risk Management–20 (HCR-20) risk factors and Structured Assessment of Protective Factors for violence risk (SAPROF) protective factors at different treatment stages were compared with violent incidents during treatment for 399 multidisciplinary coded assessments on 185 male and female forensic psychiatric patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 44 publications
4
30
2
Order By: Relevance
“…The fact that the SAPROF Japanese version had predictive validity is consistent with a previous study conducted among a Dutch sample of inpatients [ 21 ]. In this Dutch inpatient study, most of the patients (89%) had been diagnosed with at least one personality disorder (particularly Cluster B disorders), while 53% of the patients had been diagnosed with a major mental illness (primarily psychotic disorders, such as schizophrenia) [ 21 ]. The duration of observation for violence was 12 months after the initial assessment.…”
Section: Discussionsupporting
confidence: 89%
“…The fact that the SAPROF Japanese version had predictive validity is consistent with a previous study conducted among a Dutch sample of inpatients [ 21 ]. In this Dutch inpatient study, most of the patients (89%) had been diagnosed with at least one personality disorder (particularly Cluster B disorders), while 53% of the patients had been diagnosed with a major mental illness (primarily psychotic disorders, such as schizophrenia) [ 21 ]. The duration of observation for violence was 12 months after the initial assessment.…”
Section: Discussionsupporting
confidence: 89%
“…The SAPROF and the START Strength scores did not demonstrate significant predictive validity in this female sample. In a previous study, the SAPROF showed better results for women (de Vries Robbé et al, 2016). However, in the referred study, the SAPROF was examined for inpatient violence and not for recidivism after discharge.…”
Section: Discussionmentioning
confidence: 86%
“…Given the severe consequences of inpatient physical violence for victims, it is important to be able to assess, upon admittance, which patients have higher risks to threaten ward safety. The available evidence suggests, however, that the predictive properties of one of the most widely used violent risk assessment instruments (Ramesh et al, 2018), that is, the Historical Clinical Risk Management–20 (Webster et al, 1997), were good during the later phases of treatment, but less during the early treatment phases (de Vries Robbé et al, 2016). Therefore, more research on physically violent inpatients is necessary.…”
Section: Identifying Physically Violent Inpatientsmentioning
confidence: 99%